ANALISIS MEDIA SOSIAL TIKTOK DALAM PEMBENTUKAN KARAKTER SOPAN SANTUN KELAS V SDN LANGENHARJO 02 PATI - Ahmad Elwi Yusro; AY Soegeng Ysh; Eka Sari Setianingsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that drives this research is the low character of students' environmental care and the absence of innovative character education at Kalicari 02 State Elementary School. The solution to this problem is the Development of an Outbound-Based Game Model in Environmental Care Character in Fifth Grade Elementary School Students. The problem formulations in this study are 1) How is the validity and feasibility of developing an Outbound-based Game Model in Environmental Care Characters in Grade V Elementary School Students, 2) How is the effectiveness of the Outbound-based Game Model in Environmental Care Character in Primary School Grade V Students in improving students' environmental care character. The objectives of this study are 1) To determine the validity and feasibility of developing an outbound-based game model in the character of environmental care in grade V elementary school students, 2) To determine the effectiveness of the Outbound-based Game Model in Environmental Care Character in Grade V Elementary School Students in improving students' environmental care character. The type of research used in this study is research and development (Research and Development) with the ADDIE development model (Analyze, Design, Develop, Implementation, Evaluation). The resulting product is an outbound-based game model in the character of environmental care that has been implemented at Kalicari 02 State Elementary School. The Outbound-Based Game Model in Environmental Care Character in Class V Elementary School Students received model validation results of 85% and 95% with "very feasible" criteria and material validation results of 88% and 93% with "very feasible" criteria. The results of the teacher response practicality questionnaire get a percentage of 91% with the criteria "very feasible". The results of the student questionnaire before treatment obtained a percentage of 60% with the criterion "not feasible". Then for the results of the student questionnaire after treatment obtained a percentage of 88% with the criteria "very feasible". It can be concluded that the Development of Outbound-Based Game Models in Environmental Care Characters in Grade V Elementary School Students is valid, feasible to use and can improve the environmental care character of elementary school students. Based on the results of this study, the suggestion that can be provided is that the outbound-based game model in environmental care character can be used as an alternative teacher in improving students' environmental care character.